Comprehensive Physiology 2011
DOI: 10.1002/cphy.c090018
|View full text |Cite
|
Sign up to set email alerts
|

Hibernation and Gas Exchange

Abstract: Hibernation in endotherms and ectotherms is characterized by an energy-conserving metabolic depression due to low body temperatures and poorly understood temperature-independent mechanisms. Rates of gas exchange are correspondly reduced. In hibernating mammals, ventilation falls even more than metabolic rate leading to a relative respiratory acidosis that may contribute to metabolic depression. Breathing in some mammals becomes episodic and in some small mammals significant apneic gas exchange may occur by pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 186 publications
0
23
0
Order By: Relevance
“…In mountain ranges of western North America, burrow-dwelling rodents in the squirrel family (Sciuridae) are common denizens of the alpine and subalpine zones, most notably the golden-mantled ground squirrel (Callospermophilus lateralis) and the yellow-bellied marmot (Marmota flaviventris), which occur at the highest possible elevations in the contiguous United States (Armstrong, 1972;Chappell and Dlugosz, 2009). In addition to the hypoxic challenges associated with life underground and life at high altitude, many sciurid rodents face additional gas transport challenges associated with depressed ventilation and episodic breathing during winter hibernation (Milsom, 1992;Milsom and Jackson, 2011;Webb and Milsom, 1994). In hibernating ground squirrels, prolonged periods of apnea can result in wide fluctuations in arterial P O2 and plasma pH (Maginniss and Milsom, 1994;Malan et al, 1973;Musacchia and Volkert, 1971).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mountain ranges of western North America, burrow-dwelling rodents in the squirrel family (Sciuridae) are common denizens of the alpine and subalpine zones, most notably the golden-mantled ground squirrel (Callospermophilus lateralis) and the yellow-bellied marmot (Marmota flaviventris), which occur at the highest possible elevations in the contiguous United States (Armstrong, 1972;Chappell and Dlugosz, 2009). In addition to the hypoxic challenges associated with life underground and life at high altitude, many sciurid rodents face additional gas transport challenges associated with depressed ventilation and episodic breathing during winter hibernation (Milsom, 1992;Milsom and Jackson, 2011;Webb and Milsom, 1994). In hibernating ground squirrels, prolonged periods of apnea can result in wide fluctuations in arterial P O2 and plasma pH (Maginniss and Milsom, 1994;Malan et al, 1973;Musacchia and Volkert, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in hibernating mammals, a left-shifted blood-O 2 equilibrium curve can help safeguard arterial O 2 saturation during apneic periods and prevent unfavorable O 2 release to tissues (Maginniss and Milsom, 1994;Milsom and Jackson, 2011;Revsbech et al, 2013). An increase in blood-O 2 affinity can be achieved by changes in the intrinsic O 2 affinity of hemoglobin (Hb), changes in the sensitivity of Hb to allosteric effectors and/or changes in the concentrations of allosteric effectors within the erythrocyte.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of substantial downregulation of ventilation and heart rate, most hibernators likely experience only slight or no hypoxia and in some ground squirrels arterial O 2 tension (PO 2 ) is normal during torpor (16). As opposed to smaller hibernators that exhibit periods of spontaneous arousals back to normothermic temperature and metabolic rate (33,31), bears do not arouse to normothermic temperature during winter but have shallow multiday cyclic (1.6 -7.3 days) fluctuations in body temperature (43). Nevertheless, as demonstrated in a recent study (43), bears exhibit a strong active aerobic metabolic depression and a weight-specific metabolic rate similar to that of smaller hibernators (20,25,43), and for this reason, they are now recognized as true hibernators, even though they do not show the dramatic drop in body temperature and arousals typical of small hibernators (43).…”
mentioning
confidence: 99%
“…Previous experimental data demonstrated peculiar neurotransmitter characteristics typical of different brain regions. Indeed, it has to be considered that in hibernating species, some neurons generate and conduct impulses and initiate synaptic transmission at the low temperature associated with deep torpor, albeit with reduced capacities (Harris & Milsom 1995;Milsom & Jackson 2011). On the other hand, recent studies in hamster demonstrated that during the torpor phase of hibernation several metabolites, i.e.…”
Section: Neurotransmissionmentioning
confidence: 99%